The semiotics of diplomatic dialogue: pomp and circumstance in Tsar Peter I's visit to Vienna in 1698 - Hennings, J (International Hisory Review, Simon Fraser University, British Columbia, Canada, 2008)
This article investigates the semiotic dimensions of Tsar Peter I's Grand Embassy to the court of the Holy Roman Emperor, Leopold I, as an example of the role of politics in ceremony and ceremony in politics. It ignores the reason for Peter I's visit to Vienna - his wish to persuade Emperor Leopold I to prolong the war with the Ottoman empire - and does not dissect the ceremonies for evidence of the differences between Habsburg and Muscovite traditions. Rather, it asks how far ceremony constrained or facilitated political communication. Peter I's embassy to Vienna illustrates the theatricality of diplomatic dialogue in the age of baroque culture; the way in which rulers and statesmen changed the scenery in the theatre of honour and glory in order to reconcile seemingly incompatible ceremonial demands and to forward negotiations with other states. However rigid were the rules governing precedence, and however greatly they constrained rulers as well as their subjects, ceremonies were understood to be a system of signs, to be adjusted and manipulated short of undermining the established hierarchical system. The crucial arena for such manoeuvres was the court. The degree to which spectators, most often aristocrats and courtiers, took part determined the degree to which symbolic communication between the negotiating parties was perceived to be binding. In 1698, the relations between the tsar and emperor necessitated the communication of conflicting political messages. These passed through three separate, if interconnected, channels of communication that followed distinct sets of semiotic rules and involved substantiated, the established hierarchical relationship between tsar and emperor in the international system. Second, private ceremonies facilitated a personal relationship between two royal allies, portrayed as equal brothers. Third, the negotiations about the Ottoman war were kept secret, away from public view, to prevent the disagreements over the war from challenging the symbolically established order and striking at the foundations of monarchical authority.